Literasi Keuangan sebagai Moderator Pelemah: Bukti Empiris Program Kredit Usaha Rakyat pada UMKM Kota Mataram - Ismayadi Armansyah; Burhanudin Burhanudin; Nila Rahayu (Owner : Riset dan Jurnal Akuntansi, 2026)
MSMEs are still burdened by limited access to capital and suboptimal financial performance. The People's Business Credit (KUR) program is seen as a policy solution, but evidence of its utilization mechanism is still limited. This quantitative study examines the effect of KUR on the financial performance of MSMEs in Mataram City and the moderating role of financial literacy in a sample of 100 respondents using SEM-PLS analysis. The results show that KUR has a positive and significant effect on financial performance indicators (turnover, profit, and capital capacity). Meanwhile, financial literacy functions as a counterbalancing moderator that reduces the effectiveness of KUR, indicating a mechanism of prudence that restrains credit utilization. These findings not only strengthen empirical evidence on the benefits of access to financing, but also offer a theoretical contribution, namely that financial literacy does not always act as a reinforcer. The financial literacy theory model needs to be expanded to accommodate negative moderation effects through financial behavior mechanisms and fund usage selectivity. Practically, the results emphasize that KUR policies should combine credit distribution with behavioral interventions and operational assistance so that financing programs can encourage productive investment rather than merely increasing fund usage conservatism.